Exploring the antecedents and consequences of effectuation in NPD: the moderating role of firm size. Issue 7 (3rd July 2022) - Deng, Cheng; Yang, Jianjun; Loh, Lawrence; Mu, Tian
ABSTRACT: Using survey data from 291 Chinese firms, we explore the potential antecedents and consequences of effectuation in new product development (NPD) activities, as well as investigating the moderating role of firm size. We find that effectuation has a positive effect on new product creativity (NPC). We further find that both environmental dynamism (ED) and slack resources (SR) have a positive effect on effectuation. In terms of the moderating role of firm size, we find it weakens the relationship between ED and effectuation, but strengthens the relationship between SR and effectuation. Our findings support the active role effectuation plays in boosting NPC and extend existing understanding of how ED and SR promote effectuation respectively. The study also highlights the different moderating roles of firm size between two antecedents and effectuation.